2016
DOI: 10.1016/j.bmc.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pharmacological evaluation of nucleoside prodrugs designed to target siderophore biosynthesis in Mycobacterium tuberculosis

Abstract: The nucleoside antibiotic, 5′-O-[N-(salicyl)sulfamoyl]adenosine (1), possesses potent whole-cell activity against Mycobacterium tuberculosis (Mtb), the etiological agent of tuberculosis (TB). This compound is also active in vivo, but suffers from poor drug disposition properties that result in poor bioavailability and rapid clearance. The synthesis and evaluation of a systematic series of lipophilic ester prodrugs containing linear and α-branched alkanoyl groups from two to twelve carbons at the 3′-position of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
0
18
0
3
Order By: Relevance
“…[40] They again concluded that C2'-fluorination (R 4 )w as the most successful modification, with activity maintained against MbtA whilst improving the PK properties.E nhancement of the lipophilicity and prodrug approaches,f or example,e ster prodrugs of C2'fluorosulfamide isostere 21 versus parent compound 20 led to inferior PK data (plasma stability at t 1/2 typically lower than that of 20). [41] An inherent limitation of 17 is degradation through the formation of cyclonucleosides. [42] Although this does not occur in 8-aza-3-deaza-adenines (e.g.…”
Section: Biosynthesis Of Siderophoresmentioning
confidence: 99%
“…[40] They again concluded that C2'-fluorination (R 4 )w as the most successful modification, with activity maintained against MbtA whilst improving the PK properties.E nhancement of the lipophilicity and prodrug approaches,f or example,e ster prodrugs of C2'fluorosulfamide isostere 21 versus parent compound 20 led to inferior PK data (plasma stability at t 1/2 typically lower than that of 20). [41] An inherent limitation of 17 is degradation through the formation of cyclonucleosides. [42] Although this does not occur in 8-aza-3-deaza-adenines (e.g.…”
Section: Biosynthesis Of Siderophoresmentioning
confidence: 99%
“…In den neuesten Ansätzen wurden von Aldrich und Mitarbeitern 2'-u nd 3'-Fluor-Analoga zu einem Sulfamid-Isoster 18 [39] synthetisiert, wobei die Zucker den "nçrdlichen" (C3'-endo,C 2 '-exo)o der "südlichen" (C2'-endo,C3'-exo)T eil einnehmen (Abbildung 6). [41] Eine inhärente Einschränkung von 17 ist der Abbau über die Bildung eines Cyclonucleosides. Die Erhçhung der Lipophilie oder Prodrug-Ansätze,w ie Estervorstufen des C2'-Fluorsulfonamid-Isosters 21 im Vergleich zur ursprünglichen Substanz 20 verschlechterten die PK-Eigenschaften (Plasmastabilitätw urde geringer).…”
Section: Biosynthese Von Siderophorenunclassified
“…Die Erhçhung der Lipophilie oder Prodrug-Ansätze,w ie Estervorstufen des C2'-Fluorsulfonamid-Isosters 21 im Vergleich zur ursprünglichen Substanz 20 verschlechterten die PK-Eigenschaften (Plasmastabilitätw urde geringer). [41] Eine inhärente Einschränkung von 17 ist der Abbau über die Bildung eines Cyclonucleosides. [42] Obwohl dies bei den 8-Aza-3-deaza-Adeninen (z.…”
Section: Eisenaufnahme:e Inunclassified
See 1 more Smart Citation
“…Nucleoside derivatives have historically served as potent antiviral and anticancer agents [3], but it was not until 2000 that their anti-TB activity was reported [4]. Recently, several reports of modified nucleosides showing activity against Mycobacterium tuberculosis (M. tuberculosis) , Mycobacterium bovis (M. bovis) and Mycobacterium avium (M. avium) were published [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. Among them, the best activity was observed for several uridine analogues (MIC 90 1 to 10 µg/mL) possessing 5-alkynyl (decynyl, dodecynyl, tetradecynyl, pyridylethynyl, etc.)…”
Section: Introductionmentioning
confidence: 99%